2019
DOI: 10.15171/apb.2019.073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunogenic Effect of Toxoplasma gondii RecombinantSAG-1 Antigen with Propranolol as Adjuvant in BALB/c Mice

Abstract: Purpose: Propranolol as a novel adjuvant, was used to evaluate the immunogenic effect of three doses of recombinant SAG-1 (rSAG-1) antigen of Toxoplasma gondii in BALB/c mice for finding the optimal dose, and was compared with efficacy of tachyzoite lysate antigen (TLA). Methods: Eight different groups of 15 BALB/c mice received different volumes of the immunogenic material (three doses of r SAG-1 and one dose of TLA antigens), with or without propranolol adjuvant, subcutaneously. The control group mice receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In 2019, Abbasi et al performed a study on T. gondii SAG1 antigens in BALB/c mice, and their results indicated that PRP-receiving groups with SAG1 antigen increased IFN-γ production and elevated immune system shift to TH1. 35 By comparing the MTT assay and the survival rate of the mice, we found that these tests are high in the groups using alum-PRP and higher in the PRP-receiving groups. In Abbasi et al’s study, IL-5 levels were higher in the TLA-recipient group, whereas in our study, the group used alum with the antigen was the highest.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In 2019, Abbasi et al performed a study on T. gondii SAG1 antigens in BALB/c mice, and their results indicated that PRP-receiving groups with SAG1 antigen increased IFN-γ production and elevated immune system shift to TH1. 35 By comparing the MTT assay and the survival rate of the mice, we found that these tests are high in the groups using alum-PRP and higher in the PRP-receiving groups. In Abbasi et al’s study, IL-5 levels were higher in the TLA-recipient group, whereas in our study, the group used alum with the antigen was the highest.…”
Section: Discussionmentioning
confidence: 85%
“…As already demonstrated, Th1 cells are responsible for cell-mediated immunity, whereas Th2 responses support humoral immunity. 35 Thus, the immunity induced by the administration of dual adjuvants with the ESA vaccine was biased toward cell-mediated rather than humoral immunity. Furthermore, alum-PRP mixture used as an adjuvant increased the proliferation of lymphocytes and improved resistance characterized by the prolonged survival time of mice challenged with T. gondii RH strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, an immune response that induces the production of IgG2a and/or IgG2b antibodies is mainly mediated by Th1 cells, whereas the production of IgG1 antibodies is mediated by Th2 cells (Snapper and Paul, 1987;Snapper et al, 1988;Stevens et al, 1988). Several reports showed that adjuvant-free recombinant SAG1 used in mouse immunizations does not enhance an effective humoral response against T. gondii infection or enhance a non-protective Th2 antibody response (Naeem et al, 2018;Abasi et al, 2019;Sánchez-López et al, 2019;Pagheh et al, 2020). In fact, SAG1 immunization was always analyzed with an adjuvant to generate a strong Th1 immune response (Wang and Yin, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…T he intracellular parasite, Toxoplasma gondii , is a cosmopolitan apicomplexan protosa important in human and veterinary medicines( 1 – 2 ). It is one of the most significant zoonotic feline gastrointestinal parasites transmitted to humans without the help of intermediate hosts or vectors ( 3 ).…”
Section: Introductionmentioning
confidence: 99%